Financial Well-Being as a Management Strategy: Linking Employee Well-Being to Company Performance - Adrian Eka Darma Serang; Nasrullah Djamil; Tiara Nirmala; IGP Ratih Andaningsih (Nomico, 2025)
Employee financial well-being is a strategic aspect of human resource management that directly impacts psychological stability, motivation, and individual performance. A stable financial condition reduces economic stress, allowing cognitive capacity to focus on achieving work targets and increasing productivity. This study used a qualitative method with a literature review approach to analyze the relationship between financial well-being and company performance, while also identifying effective implementation strategies. The results of the literature synthesis indicate that financial well-being contributes to reduced turnover rates, absenteeism, and work errors, as well as strengthening a positive work culture and team cohesion. Support programs such as financial literacy, access to soft financing, and insurance protection serve as psychological buffers and instruments for mitigating external risks. Integrating these concepts into HR policies supports the achievement of Sustainable Human Resource Management (SHRM) and internal Corporate Social Responsibility (CSR) goals. Furthermore, the positive reputation created strengthens employer branding, attracts quality talent, and creates a competitive advantage that is difficult to replicate. Thus, financial well-being is not merely a welfare policy, but rather a strategic foundation that synergizes an organization's economic, social, and cultural goals in a sustainable manner